2005
DOI: 10.1091/mbc.e05-04-0338
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging ofDrosophilaBrain Neuroblasts Reveals a Role for Lis1/Dynactin in Spindle Assembly and Mitotic Checkpoint Control

Abstract: Lis1 is required for nuclear migration in fungi, cell cycle progression in mammals, and the formation of a folded cerebral cortex in humans. Lis1 binds dynactin and the dynein motor complex, but the role of Lis1 in many dynein/dynactindependent processes is not clearly understood. Here we generate and/or characterize mutants for Drosophila Lis1 and a dynactin subunit, Glued, to investigate the role of Lis1/dynactin in mitotic checkpoint function. In addition, we develop an improved time-lapse video microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 69 publications
11
138
1
Order By: Relevance
“…1j--m; Supplementary Fig. 1) Lis1 enhances Dynein--mediated minus end--directed transport along microtubules, and previous characterization of tagged Lis1 revealed that this marker is transported towards microtubule minus ends during mitosis and meiosis 24,25 . We found that dendritic localization of tagged Lis1 24,25 also differed between class I and IV neurons, and was regulated by ab.…”
Section: Neuron Class--specific Arrangements Of the Microtubule Arraymentioning
confidence: 73%
“…1j--m; Supplementary Fig. 1) Lis1 enhances Dynein--mediated minus end--directed transport along microtubules, and previous characterization of tagged Lis1 revealed that this marker is transported towards microtubule minus ends during mitosis and meiosis 24,25 . We found that dendritic localization of tagged Lis1 24,25 also differed between class I and IV neurons, and was regulated by ab.…”
Section: Neuron Class--specific Arrangements Of the Microtubule Arraymentioning
confidence: 73%
“…Freshly hatched WT pins P62 and G␣i P8 zygotic mutant larvae were aged for 96-120 h at 25°C and prepared for immunofluorescent antibody labeling as described previously, with the modification that 5% normal goat serum was added to the larval blocking and primary antibody solutions (32). Primary antibodies were rat anti-Pins [#2, 1:500 (9)], rabbit anti-G␣i (1:500; raised against peptide, amino acids 327-355), rabbit anti-Insc (1:1,000; W. Chia), rabbit anti-Mud (raised against amino acids 375-549; 1:2,000; H. Nash), mouse anti-␣-tubulin (1:2,000; DM1A, Sigma), and mouse-anti-HA (1:1,000; Covance).…”
Section: Methodsmentioning
confidence: 99%
“…32. Brains were imaged by using a Bio-Rad Radiance 2100 laser scanning confocal microscope equipped with a ϫ60 1.4-N.A.…”
Section: Analysis Of Spindle Orientation In Fixed and Live Larval Neumentioning
confidence: 99%
“…Faulkner et al 165 observed that LIS1 expression levels correlate with the length of the cell cycle. In mammals, Drosophila and Caenorhabditis elegans LIS1, NDEL1 and NDE1 are all required for formation of the mitotic spindle, 165,166 while LIS1 and NDEL1 are also implicated in checkpoint control of the cell cycle. 167 It is therefore possible that these proteins influence cortical development by modulating neuronal proliferation in the ventricular zone, 156 as well as by regulating migration of newborn neurons from the ventricular zone to the cortical plate.…”
Section: Lis1 Ndel1 Nde1 and Disc1mentioning
confidence: 99%